Protective Effects of Methylsulfonylmethane on Hemodynamics and Oxidative Stress in Monocrotaline-Induced Pulmonary Hypertensive Rats - Sadollah Mohammadi; Moslem Najafi; Hossein Hamzeiy; Nasrin Maleki-Dizaji; Masoud Pezeshkian; Homayon Sadeghi-Bazargani; Masoud Darabi; Sara Mostafalou; Shahab Bohlooli; Alireza Garjani (Advances in Pharmacological Sciences)
Methylsulfonylmethane (MSM) is naturally occurring organic sulfur that is known as a potent antioxidant/anti-inflammatory compound. The aim of this study was to investigate the effect of MSM on hemodynamics functions and oxidative stress in rats with monocrotaline- (MCT-) induced pulmonary arterial hypertension (PAH). Wistar rats were randomly assigned to 38-days treatment. MSM was administered to rats at 100, 200, and 400 mg/kg/day doses 10 days before a single dose of 60 mg/kg, IP, MCT. Hemodynamics of ventricles were determined by Powerlab AD instrument. Blood samples were obtained to evaluate changes in the antioxidative system including activities of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), and the level of reduced glutathione (GSH) and malondialdehyde (MDA). Improvements in cardiopulmonary hemodynamics were observed in the MSM-treated pulmonary arterial hypertensive rats, with a significant reduction in right ventricular systolic pressure (RSVP) and an increase in the mean arterial pressure (MAP). The values of CAT, SOD, GSH-px activities, and GSH were significantly lower in MCT-induced PAH (P<0.01), but they were recovered to control levels of MSM-treated groups. Our present results suggest that long-term administration of the MSM attenuates MCT-induced PAH in rats through modulation of oxidative stress and antioxidant defense.